Root tolerance and biochemical response of Chinese lettuce (Lactuca sativa L.) genotypes to cadmium stress - Dawuda, Mohammed Mujitaba; Liao, Weibiao; Hu, Linli; Yu, Jihua; Xie, Jianming; Calderón-Urrea, Alejandro; Jin, Xin; Wu, Yue (PeerJ, 2019)
This study was conducted to determine the root tolerance and biochemical responses of four Chinese Lactuca sativa L. genotypes (Lüsu, Lümeng, Yidali and Anyan) to cadmium (Cd2+) stress. Twenty-eight days old seedlings were exposed to Hoagland’s nutrient solution supplied with or without 100 µM CdCl2 and monitored for seven days in a climate controlled room. The 100 µM CdCl2 significantly (P < 0.001) decreased all the root morphological indexes of the four genotypes. However, Yidali, which possessed the smallest root system, exhibited greater root tolerance to Cd2+ by having the highest tolerance indexes for root volume (46%), surface area (61%), projected area (74%) and numbers of root forks (63%) and root tips (58%). Moreover, Cd2+ stress also caused increases in H2O2 contents in the roots but the increase was least in Yidali which showed greater root tolerance to Cd2+stress. The effect of Cd2+ stress on the contents of hormones in the roots depended on the genotypes. Under Cd2+ stress, abscisic acid correlated positively with indole-3-acetic acid (r = 0.669*), gibberellic acid (r = 0.630*) and cytokinin (r = 0.785**). The antioxidant enzyme activities and proline responses of the four genotypes to Cd2+ stress were similar. The SOD activity was decreased whiles the CAT and POD activities, as well as the contents of proline increased in all the genotypes under the stress condition. These results suggest that lettuce genotypes with smaller root systems could be more tolerant to Cd2+ stress compared to those with larger root systems.
Keywords: Cadmium stress; Antioxidant enzymes; Endogenous hormones; Lettuce genotypes; Root morphology